Race, racialisation and colour-caste - George Hull (The Thinker)
Since race categories do not pick out biologically significant divisions of humanity, their use can be misleading and offensive. Yet racialisation – society’s viewing and treating South Africans as though they comprised different races – has generated real societal groups which are significant from the perspectives of justice and identity. In the philosophy of race, these facts make for a conceptual conundrum. Is common-sense race thinking right that races, if they exist, are human groups differing in significant, inherent and heritable ways, in which case there are no races? Or has common-sense race thinking failed to grasp races’ socially constructed nature, and should we say races are the really existing groups generated by racialisation? The same facts confronted the Non-European Unity Movement (NEUM) – a mid-20th-century South African liberation movement – with an organisational and theoretical challenge. Given its uncompromising non-racialism, how could it justify a federal structure which effectively divided its membership into African, Coloured, and Indian sections? If this was not race-based division, what was it? A former NEUM member, Neville Alexander, provided the Unity Movement with the conceptual resources to answer this challenge. I argue that his major work, One Azania, One Nation, is also a contribution to the philosophy of race. Alexander first contends that social constructionists cannot, without equivocation, claim that common-sense thinking about race in one sense has created races in a quite different sense. He then shows that introducing a second concept, ‘colour-caste’, can preserve the insights of the constructionist approach. While races are unreal, colour-castes are real social identities which need to be overcome.